Convective-core overshooting and the final fate of massive stars - Temaj, Duresa; Schneider, Fabian; Laplace, Eva; Wei, D.; Podsiadlowski, Philipp (Astronomy and astrophysics, 2024)
A massive star can explode in powerful supernova (SN) and form a neutron star, but it may also collapse directly into a black hole. Understanding and predicting the final fate of such stars is increasingly important, for instance, in the context of gravitational-wave astronomy. The interior mixing of stars (in general) and convective boundary mixing (in particular) remain some of the largest uncertainties in their evolution. Here, we investigate the influence of convective boundary mixing on the pre-SN structure and explosion properties of massive stars. Using the 1D stellar evolution code MESA, we modeled single, non-rotating stars of solar metallicity, with initial masses of 5 − 70 M⊙ and convective core step-overshooting of 0.05 − 0.50 pressure scale heights. Stars were evolved until the onset of iron core collapse and the pre-SN models were exploded using a parametric, semi-analytic SN code. We used the compactness parameter to describe the interior structure of stars at core collapse and we found a pronounced peak in compactness at carbon-oxygen core masses of MCO ≈ 7 M⊙, along with generally high compactness at MCO ≳ 14 M⊙. Larger convective core overshooting will shift the location of the compactness peak by 1 − 2 M⊙ to higher MCO. These core masses correspond to initial masses of 24 M⊙ (19 M⊙) and ≳40 M⊙ (≳30 M⊙), respectively, in models with the lowest (highest) convective core overshooting parameter. In both high-compactness regimes, stars are found to collapse into black holes. As the luminosity of the pre-supernova progenitor is determined by MCO, we predict black hole formation for progenitors with luminosities of 5.35 ≤ log(L/L⊙)≤5.50 and log(L/L⊙)≥5.80. The luminosity range of black hole formation from stars in the compactness peak is in good agreement with the observed luminosity of the red supergiant star N6946 BH1, which disappeared without a bright supernova, indicating that it had likely collapsed into a black hole. While some of our models in the luminosity range of log(L/L⊙) = 5.1 − 5.5 do indeed collapse to form black holes, this does not fully explain the lack of observed SN IIP progenitors at these luminosities. This case specifically refers to the “missing red supergiant” problem. The amount of convective boundary mixing also affects the wind mass loss of stars, such that the lowest black hole masses are 15 M⊙ and 10 M⊙ in our models, with the lowest and highest convective core overshooting parameter, respectively. The compactness parameter, central specific entropy, and iron core mass describe a qualitatively similar landscape as a function of MCO, and we find that entropy is a particularly good predictor of the neutron-star masses in our models. We find no correlation between the explosion energy, kick velocity, and nickel mass production with the convective core overshooting value, but we do see a tight relation with the compactness parameter. Furthermore, we show how convective core overshooting affects the pre-supernova locations of stars in the Hertzsprung–Russell diagram (HRD) and the plateau luminosity and duration of SN IIP light curves.
Online veröffentlicht: 12. Februar 2024
Gesehen am 07.06.2024